2019
DOI: 10.1007/s00421-019-04124-7
|View full text |Cite
|
Sign up to set email alerts
|

Is reaction time altered by mental or physical exertion?

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag GmbH Germany, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
5
13
0
2
Order By: Relevance
“…Analysis of the results of almost all tests allows us to consider the condition of the athletes similar. Our data are close Le Mansec et al [19]. The authors evaluated the dynamics of the response time depending on different loads.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of the results of almost all tests allows us to consider the condition of the athletes similar. Our data are close Le Mansec et al [19]. The authors evaluated the dynamics of the response time depending on different loads.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, no previous studies have quantified the mental fatigue caused by a real competition in racket sports. However, previous studies confirmed that performing cognitively fatiguing tasks can increase mental fatigue in professional racket sports players [11][12][13][14]. Indeed, Thompson et al [22] and Smith et al [23] highlighted the need to implement this type of ecological study, because this information allows coaches to know the true psychological demands during competitions and to understand how they can train these demands in simulated training contexts.…”
Section: Mental Fatiguementioning
confidence: 99%
“…A limited number of studies have looked into the effects of mental fatigue on racket sport performance, but the outcome is not straightforward. Kosack et al [11] have not reported impairments in a badminton specific test after a mental exertion task, and Le Mansec et al [12] have not reported negative effects of mental fatigue on reaction time, an important variable in this type of sport. On the other hand, Le Mansec et al [13] reported a decrease in the speed of the ball in table tennis players after a mental exertion task, probably to maintain the accuracy of the shots in the presence of mental fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Waktu reaksi belum terganggu jika reaksi yang diminta adalah reaksi yang sederhana (Le Mansec, Dorel, Nordez, & Jubeau, 2019), tetapi kelelahan fisik dan mental berkorelasi negatif terhadap waktu reaksi (Le Mansec et al, 2019). Dengan kemampuan respon yang lambat merupakan salah satu faktor yang merugikan dalam olahraga (Eckner et al, 2015).…”
unclassified
“…Le Mansec et al, 2019), sehingga waktu yang diperlukan untuk merespon untuk bergerak sangat menentukan keberhasilan dalam pertandingan.METODEPenelitian ini dilakukan dengan survey. Dilakukan tes dan pengukuran terhadap waktu reaksi dengan dua sinyal.…”
unclassified